Family violence effects on children - Deza Villanueva, Sabina (2004)
Family violence effects on children and adolescents are analyzed in this research. Child maltreatment definitions as well as its characteristics scopes are determined. Besides, some significant aspects of their progenitors are point out. Finally, according to an evolutional point of view, influence of family violence on the child- adolescent development is expressed.